THE CREATION OF THE LAEM PHO BOAT SONG PERFORMANCE: A CULTURAL IDENTITY OF THE LAEM PHO COMMUNITY IN KHU TAO SUBDISTRICT, HAT YAI DISTRICT, SONGKHLA PROVINCE - Srichai, Rawasara; Potiwetchakul, Supavadee (Journal of MCU Nakhondhat, 2024)
This research aims to create a performance of the "Laem Pho Boat Song" to communicate the identity of the Laem Pho community, Khu Tao Subdistrict, Hat Yai District, Songkhla Province. It employs a mixed-methods approach. Key informants include local scholars, academics, folk artists, and National Artists in the field of folk performing arts, selected through purposive sampling. The research tools consist of observation forms and in-depth interviews. Data were collected through interviews with relevant stakeholders and small group discussions, followed by data analysis leading to the development of the performance. The findings reveal that the creative performance of the Laem Pho Boat Song takes the form of a theatrical production, utilizing the local landscape and involving community members in expressing the cultural capital of Laem Pho's identity. The concept focuses on conveying the tradition of "Chak Phra" (water procession), which originates from Laem Pho and represents a multifaceted cultural capital integral to the way of life of Laem Pho's people. This area is not only a cultural space but also a sacred site. The performance integrates elements of the Laem Pho Boat Song and folk dance, set against the natural landscape of Laem Pho, with a clear and accessible narrative. The scenic design highlights the beauty of the waters surrounding the area. The performance begins by introducing the social context of Laem Pho, its geography, traditional wisdom such as the making of "Kanom Tom" (a local dessert), the Chak Phra tradition with decorated boats, the local merit-making tradition during the Buddhist Lent, and the performance of the Laem Pho Boat Song on land as a form of courtship.